Vertical division of labour: a sociology of the work of remote organisers. (1st January 2019) - Dujarier, Marie-Anne
Abstract : Contemporary work organisation is characterised by a persistent vertical division of labour between managers in charge of designing work at a distance and operational workers. This article focuses on the work of specific white collar workers called 'remote organisers', and how they face the challenge of performing a task that seems impossible and socially thankless. Results from a major qualitative and quantitative survey of large French organisations and consulting firms, show that the standardisation of methods, the Taylorisation of the implementation of tasks and resorting to abstraction are what makes their work sustainable and achievable. Finally, remote organisers build up a professional norm which consists in having a playful and game-like relationship with their work.